Filosofi Teras: Filsafat Kuno untuk Mental Tangguh Masa Kini - Limbong, Ayu Miranda; Asbari, Masduki (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to review the book as an effort to explore and understand the scientific narrative of the book "Core Philosophy: Ancient Greco-Roman Philosophy for Today's Resilient Mentality" written by Henry Manampiring. This descriptive qualitative research examines the relationship between young people's personalities and today's mental toughness. This study uses a qualitative content analysis approach carried out on the book above. The author also uses secondary data sources from various articles and books related to the research object. This book is a self-development book that discusses aspects of life that are controlled through actions, attitudes and thoughts. This book invites readers to carry out an in-depth analysis of themselves in order to find their "true self".